Osteogenesis of bone marrow mesenchymal stem cell in hyperglycemia - Luo, Meng; Zhao, Zhihe; Yi, Jianru (Frontiers in Endocrinology, 2023)
Diabetes mellitus (DM) has been shown to be a clinically risk factor for bone diseases including osteoporosis and fragility. Bone metabolism is a complicated process that requires coordinated differentiation and proliferation of bone marrow mesenchymal stem cells (BMSCs). Owing to the regenerative property, BMSCs have laid a robust foundation for their clinical application in various diseases. However, mounting evidence indicate that the osteogenic capability of BMSCs is impaired under high glucose condition, which is responsible for the diabetic bone diseases and greatly reduces the therapeutic efficiency of BMSCs. With the rapidly increasing incidence of DM, a better understanding regarding the impacts of hyperglycemia on BMSCs osteogenesis and the underlying mechanisms is needed. In this review, we aim to summarize the current knowledge of the osteogenesis of BMSCs in hyperglycemia, the underlying mechanisms, and the strategies to rescue the impaired BMSCs osteogenesis.